Филип, кој (не) сакаше да кралува - Саракински, Војислав (Филозофски факултет, Скопје, 2016)
Philip of Amphaxitis, the brother of Perdiccas II, is usually said to be a pretender to the Macedonian throne. This alleged pretender, however, made absolutely no move against his brother until 432 BC, when Athens finally entered the fray. What is more, Philip neither struck coin, nor made an attempt to establish a legislative body or a state council of any sort. This, in addition to several other peculiarities of his arkhe in Amphaxitis, hints that he neither claimed the throne of the kingdom of the Argeadae, nor could he count on any level of support by the legislative bodies in Aegae. A thorough analysis of the events suggests that he simply chose to act independently and stop responding to the capital. Philip moved for the throne only after losing Amphaxitis and after securing the help and support of Derdas of Elymea and Athens: before that, he had neither power, nor a strong enough motive to fight for the royal regalia. After more than twenty years of independent rule in Amphaxitis, Philip was made a victim of Athenian political interests. In 432 BC, Athens succumbed to the needs of their Realpolitik, switched sides and gave nominal support to Perdiccas II.
Philip, who would (not) be king